2021
DOI: 10.1155/2021/9977993
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Effect of Acidic Solutions and Sodium Fluoride on Surface Roughness of Two Types of CAD-CAM Dental Ceramics

Abstract: Objectives. This study assessed the effect of immersion in acidic solutions and sodium fluoride on surface roughness of dental ceramics. Materials and Methods. 40 blocks of Vitablocs Mark II and IPS e.max CAD (5 × 5 × 3) were prepared. The samples were divided into five groups (n = 8) for immersion in artificial saliva (control), artificially prepared gastric acid, acetic acid, 0.02% sodium fluoride + gastric acid, and 0.02% sodium fluoride + acetic acid. The samples were immersed for 168 hours in the respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…According to our result, surface microhardness values of Vitablocs Mark II and IPS e.max CAD were negatively affected by the exposure to an acidic environment and sodium fluoride mouth wash. Regarding the results of the present study and those reported by the previous study [ 14 ], preventive measures involving the fluoride should be used in patients with bulimia or GERD more cautiously.…”
Section: Discussionsupporting
confidence: 69%
See 4 more Smart Citations
“…According to our result, surface microhardness values of Vitablocs Mark II and IPS e.max CAD were negatively affected by the exposure to an acidic environment and sodium fluoride mouth wash. Regarding the results of the present study and those reported by the previous study [ 14 ], preventive measures involving the fluoride should be used in patients with bulimia or GERD more cautiously.…”
Section: Discussionsupporting
confidence: 69%
“…According to a previous study [ 14 ], exposure to acidic solutions and sodium fluoride mouth wash significantly increased the surface roughness parameters of Vitablocs Mark II and IPS e.max CAD compared to immersion in saliva. These findings were also confirmed by SEM evaluations.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations